Short-term effects of Chlorhexidine mouthwash and Listerine on oral microbiome in hospitalized patients - Liu, Tsunglin; Chen, Yen-Chin; Jeng, Shuen-Lin; Chang, Jui-Jen; Wang, Jiu-Yao; Lin, Cheng-Han; Tsai, Pei-Fang; Ko, Nai-Ying; Ko, Wen-Chien; Wang, Jiun-Ling (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Chlorhexidine (CHX) and essential oil containing mouthwashes like Listerine® can improve oral hygiene via suppressing oral microbes. In hospitalized patients, CHX mouthwash reduces the incidence of ventilator-associated pneumonia. However, CHX use was also associated with increased mortality, which might be related to nitrate-reducing bacteria. Currently, no study determines oral bacteria targeted by essential oils mouthwash in hospitalized patients using a metagenomic approach. Methods We recruited 87 hospitalized patients from a previous randomized control study, and assigned them to three mouthwash groups: CHX, Listerine, and normal saline (control). Before and after gargling the mouthwash twice a day for 5-7 days, oral bacteria were examined using a 16S rDNA approach. Results Alpha diversities at the genus level decreased significantly only for the CHX and Listerine groups. Only for the two groups, oral microbiota before and after gargling were significantly different, but not clearly distinct. Paired analysis eliminated the substantial individual differences and revealed eight bacterial genera (including Prevotella, Fusobacterium, and Selenomonas) with a decreased relative abundance, while Rothia increased after gargling the CHX mouthwash. After gargling Listerine, seven genera (including Parvimonas, Eubacterium, and Selenomonas) showed a decreased relative abundance, and the magnitudes were smaller compared to the CHX group. Fewer bacteria targeted by Listerine were reported to be nitrate-reducing compared to the CHX mouthwash. Discussion In conclusion, short-term gargling of the CHX mouthwash and Listerine altered oral microbiota in our hospitalized patients. The bacterial genera targeted by the CHX mouthwash and Listerine were largely different and the magnitudes of changes were smaller using Listerine. Functional alterations of gargling CHX and Listerine were also different. These findings can be considered for managing oral hygiene of hospitalized patients.